2015
DOI: 10.1007/s11060-015-1770-9
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for atypical meningiomas

Abstract: We report clinical outcomes of proton therapy in patients with World Health Organization grade 2 (atypical) meningiomas. Between 2005 and 2013, 22 patients with atypical meningiomas were treated to a median dose of 63 Gy (RBE) using proton therapy, as an adjuvant therapy after surgery (n=12) or for recurrence or progression of residual tumor (n=10). Six patients had presumed radiation-induced meningiomas, but none had received prior radiotherapy for their meningioma. The median follow-up time after radiation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
(29 reference statements)
2
23
0
1
Order By: Relevance
“…Multiple retrospective series have suggested that dose escalation beyond 60 Gy is correlated with improved long-term tumor control in patients with atypical or malignant meningiomas (68). In addition, prior series have reported varying rates of toxicity and have suggested that recurrent tumors portend a worse prognosis than de novo BM (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple retrospective series have suggested that dose escalation beyond 60 Gy is correlated with improved long-term tumor control in patients with atypical or malignant meningiomas (68). In addition, prior series have reported varying rates of toxicity and have suggested that recurrent tumors portend a worse prognosis than de novo BM (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Autoři uzavírají, že stutrolou 85-95 % s minimální pozdní toxicitou. Bylo realizováno 6 studií fáze II s cílem testovat potenciál protonové terapie, redukovat toxicitu u meningeomů stupně 1 a zlepšit kontrolu nádoru u stupně 2 a 3 [11][12][13][14][15][16]. Výsledky byly srovnatelné s fotonovou terapií [17].…”
Section: Cena Protonové Terapieunclassified
“…A few articles describe also the use of a mixed proton/photon beam (Table 5 [9][10][11][91][92][93][94][95][96][97][98][99][100][101][102]. From the methodological point of view, the large majority of the studies are retrospective and may include different tumour types: chordoma, chondrosarcoma, and meningioma of grade I-III.…”
Section: Proton Radiotherapymentioning
confidence: 99%
“…Local control and overall survival at 5 years were obtained in 59% and 79%, respectively, for chordoma and 75% and 100% for chondrosarcoma. 91 The review on chordoma and chondrosarcoma includes the results of proton radiotherapy delivered after one or more surgical resections (Table 5 [9][10][11][91][92][93][94][95][96][97][98][99][100][101][102] ). All series were treated to very high doses of up to 83 Gy (RBE).…”
Section: Proton Radiotherapymentioning
confidence: 99%